Automated age-at-death estimation from 3D surface scans of the facies auricularis of the pelvic bone - Štepanovský, Michal; Buk, Zdeněk; Pilmann Kotěrová, Anežka; Brůžek, Jaroslav; Bejdová, Šárka; Techataweewan, Nawaporn; Velemínská, Jana (Forensic science international, 2023)
This work presents an automated data-mining model for age-at-death estimation based on 3D scans of the auricular surface of the pelvic bone. The study is based on a multi-population sample of 688 individuals (males and females) originating from one Asian and five European identified osteological collections. Our method requires no expert knowledge and achieves similar accuracy compared to traditional subjective methods. Apart from data acquisition, the whole procedure of pre-processing, feature extraction and age estimation is fully automated and implemented as a computer program. This program is a part of a freely available web-based software tool called CoxAGE3D. This software tool is available at https://coxage3d.fit.cvut.cz/ Our age-at-death estimation method is suitable for use on individuals with known/unknown population affinity and provides moderate correlation between the estimated age and actual age (Pearson's correlation coefficient is 0.56), and a mean absolute error of 12.4 years.
Keywords: Automated analysis; faciální stigmatizace; data mining; Software; Data mining methods; Humans; Pelvic Bones; Data Mining; obličej; Facies; Face; mužské pohlaví; software; Adult age-at-death estimation; 3D surface analysis; ženské pohlaví; pánevní kosti; Auricular surface; lidé; Male; Female